Assessment of Current Situation on Emergency Preparedness for the Health Sector and Communities in Phuket, Thailand - Seetamanotch, Surangsri; Thaikruea, Lakkana; Seetamanotch, Wiwat (Journal of Health Science of Thailand, 2018)
One important issue for effective humanitarian relief is disaster preparedness that incorpo-rating all the stakeholders at all levels. This study was aimed at assessing current situation on emergency preparedness in Phuket. All target institutes from health (34) and communities (29) involving with disaster preparedness at the first 24 hours were recruited. The responsible personnel (105) from the institutes filled in the questionnaires based on their preparedness plan. Secondary data were also retrieved. A cross-sectional descriptive design was conducted on January 2007. The overall results showed that 85.6 percent of the personnel had experiences in rescuing disaster victims. For policy and management, there were 77.8 percent of institutes that had their own disaster preparedness plans while 52.5 percent of institutes had general plan for any type of disaster. The majority of the institutesี plans had assignment for responsible personnel in all sections/departments (77.5%), manpower allocation for duty (76.9%), and assigned personnel for public relation (85.0%) once disaster occurs. The common methods of recruitment personnel, if need be, were telephone (90.5%) and personal mobile phone (90.5%). For space allocation, 85 percent of the institute defined where to set a war room. The space allocations for injured victims were 47 severe cases, 160 moderate cases, 500 mild cases, 18 corpses (freezer containers). They could handle 160 suspect avian influenza/severe acute respiratory syndrome (AI/SARS) cases at outpatient department and could admit 16 AI/SARS cases. For communication and coordination, 68.2 percent of the institutes prepared lists of other institutes that involved with the disaster at a provincial level. The institutes in health sector had medicine and medical supply in stocks that could cope with 3,952 victims. Some hospitals had Advance Life Support ambulances (20) and Basic Life Support ambulances (8). Only 20.6 percent of the institutes specially set aside disaster budget for the plan. About 67.6 percent of the institutes conducted rehearsal incorporated with hospitals and 50.0 percent of them sent the personnel attending refreshing courses. There were different in preparedness between health and non-health sectors. The overall current situation on emergency preparedness in Phuket is good. However, some important issues still needs to be strengthened, including co-ordination, health information system, communication system, budget allocation, and capacity training.